The Influence of Institutional Quality towards Foreign Direct Investment (FDI) Inflows in ASEAN’s Developing Countries - Kezya Agustina Hananya; Rossanto Dwi Handoyo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
This paper discusses the influence of institutional quality on FDI stock inflows towards eight developing countries in Association of Southeast Asian Nations (ASEAN). Institution in this paper is classified in four forms, namely legal, bureaucratic, politics, and economic institutions. This paper utilizes the method of Principal Component Analysis (PCA) and panel data regression. After using PCA method to identify which variables hold the most importance, the authors then constructed an individual index for four institutions as defined before. These indices are then used for panel data regression. The result of this paper indicates that out of four forms of institutions, three institutions are found to be significant determinants. These three institutions are legal, bureaucratic, and economic institutions. Surprisingly, while bureaucratic institution has positive coefficients, the other two forms of institutions have negative coefficients, suggesting that FDI stock inflows towards developing countries in ASEAN are more likely to be motivated by weak legal and economic institutions.